The Outline of Max Weber’s Methodology of Social Cognition - Norkus, Zenonas (Problemos, 1990)
Max Weber’s (1864--1920) methodology of social cognition includes five elements. They are conceptions of: a) object’s constitution in social cognition; b) coceptualisation; c) explanation; d) understanding; e) methodological individualism. The first three conceptions are descriptive ones, the fourth is descriptive-normative, the fifth is normative.